1975
DOI: 10.1080/00039896.1975.10666631
|View full text |Cite
|
Sign up to set email alerts
|

Ozone and Human Blood

Abstract: Statistically significant changes (P less than .05) were observed in erythrocytes (RBC) and sera of young adult human males following a single short-term exposure to 0.50 ppm ozone (O3) for 2 3/4 hours. The RBC membrane fragility, glucose-6-phosphate dehydrogenase (G-6-PDH) and lactate dehydrogenase (LDH) enzyme activities were increased, while RBC acetylcholinesterase (AcChase) activity and reduced glutathione (GSH) levels were decreased. The RBC glutathione reductase (GSSRase) activities were not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
3
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(45 citation statements)
references
References 19 publications
(1 reference statement)
1
40
3
1
Order By: Relevance
“…This adaptation process may explain the changes in RBC aggregation and fragility with extended ozone application; but there was no adaptation in RBC deformability (Artis et al, 2010). It was also observed that 15 days after single dose of ozone application its effect on RBC deformability still persist but lessened (Buckley et al, 1975). Thus when talking about RBC deformability it can be said that there is either a later developing adaptation or it does not exist at all.…”
Section: Hemorheological Effects Of Ozone Treatmentmentioning
confidence: 79%
“…This adaptation process may explain the changes in RBC aggregation and fragility with extended ozone application; but there was no adaptation in RBC deformability (Artis et al, 2010). It was also observed that 15 days after single dose of ozone application its effect on RBC deformability still persist but lessened (Buckley et al, 1975). Thus when talking about RBC deformability it can be said that there is either a later developing adaptation or it does not exist at all.…”
Section: Hemorheological Effects Of Ozone Treatmentmentioning
confidence: 79%
“…Although elevated blood levels of some enzymes are indicative of tissue injury, and most authors tend to explain their findings to be those of an injurious nature, one may question whether the possibility of adaptation has been sufficiently taken into account, as was done by Buckley et al (8) and Hackney et al (9).…”
Section: Methodsmentioning
confidence: 93%
“…Even more so, since nonanthropogenic 03 is a natural ambient constituent for which an adaptive mechanism to lower values might be supposed to be present. Currently, such a mechanism has actually been suggested in the results of a number of studies, including those done in man (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The vertical axis represents GSH levels in mg%o. Normal individuals not under stress have GSH levels ranging from 53 to 84 mgo (15), while G-6-PD deficient individuals under similar nonstress conditions have approximately 70o the GSH of normal individuals with a range of 38 to 51 mg% (16). When testing for the occurrence of a G-6-PD deficiency the individual is often given a GSH stability test.…”
Section: Ozonementioning
confidence: 99%